Exploring the Interplay between Emotional Eating, Eating Behavior Traits, and Disordered Eating Behavior in Adults: A Cross-Sectional Study - Eman Fatima; Ayesha Muneer; Farryha Naeem (Nature-Nurture Journal of Psychology, 2024)
Background: Emotional eating is a significant global concern that is closely associated with weight-related outcomes in both adolescents and adults, and it often serves as a precursor to more severe eating disorders. Disordered eating behaviors are well known as important risk factors contributing to weight gain and the growth of full-syndrome eating disorders in different populations. Furthermore, eating behavior traits exhibit potential as indicators capable of recognizing tendencies towards extreme food consumption. However, previous studies have revealed separate links between emotional eating and disordered eating behavior in adults, and despite the moderating role of eating behavior traits in separate studies, the broad investigation of their combined relationship remains unexplored, and this topic is open for further debate.